Permohonan Pailit Terhadap Anak Perusahaan Badan Usaha Milik Negara : (Studi Kasus PT Indonesia Power) - Nabilla Syafira; Elisatris Gultom; Deviana Yuanitasari (International Forum of Researchers and Lecturers, 2024)
In debt and credit problems, bankruptcy is often the last solution to resolve the problem. State-Owned Enterprises or SOEs are also not immune from debt and credit problems that lead to bankruptcy. The regulation regarding the bankruptcy of SOEs itself is regulated in Article 2 Paragraph (5) of the Bankruptcy Law and its explanation. However, problems then arise when the subsidiaries of SOEs become bankruptcy respondents. There is no legislation that specifically regulates the bankruptcy of SOEs Subsidiaries, so this has led to confusion and debate in the community regarding the status of SOEs Subsidiaries in terms of bankruptcy. The ambiguity and debate can be seen in the implications of the bankruptcy petition case filed by the Kinarya Liman Margaseta Consortium against PT Indonesia Power, which is a Subsidiary of SOEs, namely PT PLN. This research aims to find out how the position of a SOEs Subsidiary in terms of bankruptcy is reviewed from the Bankruptcy Law and SOEs Law. The type of research used in this research is normative legal research. The research specifications used in this research are descriptive analysis. The approach used in this research is a statutory approach and case approach. Based on the results of this case study, it can be seen that when viewed from the Bankruptcy Law and the SOEs Law, basically the subsidiaries of SOEs and SOEs cannot be equated in status and position. This is supported by several theories and strengthened by the Constitutional Court Decision and the Supreme Court Decision. Thus, PT Indonesia Power's bankruptcy petition should be filed by its creditors in addition to the Minister of Finance.